If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-10+4x=2(x-4)+9x
We move all terms to the left:
3x-10+4x-(2(x-4)+9x)=0
We add all the numbers together, and all the variables
7x-(2(x-4)+9x)-10=0
We calculate terms in parentheses: -(2(x-4)+9x), so:We get rid of parentheses
2(x-4)+9x
We add all the numbers together, and all the variables
9x+2(x-4)
We multiply parentheses
9x+2x-8
We add all the numbers together, and all the variables
11x-8
Back to the equation:
-(11x-8)
7x-11x+8-10=0
We add all the numbers together, and all the variables
-4x-2=0
We move all terms containing x to the left, all other terms to the right
-4x=2
x=2/-4
x=-1/2
| -5-3x+8=30 | | 3x-10=5x+40 | | 5x+8x+9-36=0 | | +4x=+40 | | r/4− 4=1 | | m/4+36=41 | | 47−0u=25 | | B=3.5h=6 | | 47−u=25 | | j+40=-10+7 | | r/9+75=79 | | -122+7j=-8j-2 | | 17-4h=59 | | 59=4h−17 | | 2x-8/x=6 | | 3=×-y | | 27=46+2x-4 | | w/9=72 | | 13x-9x=-12 | | 3*x=1/729 | | f-45=30 | | 1/5×2^x=3.2 | | (2x)^x=12^12 | | -x^2+74x-1200=0 | | 7x+80=122 | | (x+8)^2-30=44 | | 4x2+4x+1=25 | | 12=-28+10c | | 6*a=48a= | | 20-e=12 | | 13=-28+10c | | 10x-6x+186=10x+90 |